The correspondence of Charles Darwin - Darwin, Charles 1809-1882 (Cambridge University Press, 2015)
This volume is part of the definitive edition of letters written by and to Charles Darwin, the most celebrated naturalist of the nineteenth century. Notes and appendixes put these fascinating and wide-ranging letters in context, making the letters accessible to both scholars and general readers. Darwin depended on correspondence to collect data from all over the world and to discuss his emerging ideas with scientific colleagues, many of whom he never met in person. The letters are published chronologically: volume 22 includes letters from 1874, the year in which Darwin completed his research on insectivorous plants and published second editions of Descent of Man and Coral Reefs. The year also saw an acrimonious dispute between Darwin and St George Jackson Mivart as a result of an anonymous review the latter had written in which he criticised Darwin's son George.
Keywords: Darwin, Charles, -- 1809-1882 -- Correspondence.